Evolution of radiobiological models: from concept generation to current knowledge about the effects of radiotherapy - Batyan, Anatoly N; Demeshko, Pavel D.; Hancharova Гончарова; Puhteeva, Irina V. (Journal of the Belarusian State University. Ecology, 2022)
The development of radiobiological models made it possible to mathematically describe biological phenomena in the body under the influence of radiation. The history of the development of radiobiological models began immediately after the discovery of X-rays and continues now, overcoming more and more restrictions. The practical application of radiobiological models is an integral part of clinical practice in cancer treatment.